(untitled) (Sociologisk Forskning, 1993)
Sociological explanation and the limits of variable analysis. A critical analysis with examples from medical sociology In this article there is presented a critical analysis of variable-oriented methodology and its possibilities of generating sociological explanations, this with concrete examples from medical sociology. Three types of causal explanations are identified: (1) causality as quantitative distributions, (2) causality as substantial and contextual relations and processes, and (3) causality as abstract properties and mechanisms. These types of causality correspond to different dimensions of the object of sociology. The article brings into focus the limited possibilities of variable analysis when it comes to: (1) bridging the often large gap between abstract structures and contextual observable actions and conditions, (2) paying regard to the contextual constitution of social properties, (3) providing new knowledge concerning the substantive content of causal relations and processes, (4) creating quasiexperimental closures anchored in the open and complex social reality, and (5) providing knowledge of internal relations and of dynamic and creative processes.